2009
DOI: 10.4076/1757-1626-2-6741
|View full text |Cite
|
Sign up to set email alerts
|

Coronary steal by left atrial mixoma: a case report

Abstract: This report describes a 41-year-old man who had atypical angina resulting from coronary steal by left atrial myxoma. The tumor was completely excised and the patient was symptoms free after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…We reviewed a number of articles on the blood supply of left atrial and right atrial myxomas. The various sources of blood supply to various myxomas reported are described in box 1 6–26The source of blood supply of some reported myxomasLeft atrial myxoma—from the right coronary artery 6–8 24…”
Section: Outcome and Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…We reviewed a number of articles on the blood supply of left atrial and right atrial myxomas. The various sources of blood supply to various myxomas reported are described in box 1 6–26The source of blood supply of some reported myxomasLeft atrial myxoma—from the right coronary artery 6–8 24…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…Left atrial myxoma—from the left circumflex 22Left atrial myxoma—from both the right coronary artery and left circumflex 19–21 23 25 26 …”
Section: Outcome and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The concept of coronary steal caused by atrial myxoma has been reported; however, those instances were diagnosed on the basis of patients' symptoms and the flow to the myxoma upon cardiac catheterization, without evidence of ischemia on stress testing. 6,7 To our knowledge, ours is the first report of a highly vascularized atrial myxoma that caused coronary steal with objective evidence of ischemia and subsequent resolution after resection of the mass and ligation of the anomalous coronary arteries. …”
Section: A Bmentioning
confidence: 99%